Sociology, Theory, and the Feminist Sociological Canon: Questioning the Use of "Doing Gender" as a Sociological Theory. (March 2017) - Davis, Shannon N.
In this article, I revisit the concept of "doing gender" to query whether the framework as directly articulated by West and Zimmerman is meant to be a description of social life (a social theory) or a testable and potentially falsifiable explanation of the empirical world (a sociological theory). I document how much of the research that uses "doing gender" is a misapplication of the concept as a social, rather than sociological, theory. I conclude by making the case for the role of "doing gender" in, rather than as, sociological theory.